THE IMPACT OF GEOPOLITICAL RISK, NET WORKING CAPITAL, RETURN ON ASSET AND DEBT TO ASSET ON CASH HOLDING IN FOOD AND BEVERAGE COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Sumarauw, Eirene Christalia Visela; Rumokoy, Lawren J.; Tumewu , Ferdinand J. (Universitas Sam Ratulangi, 2025)
This study uses a panel data regression analysis research model and a Quantitative approach. The primary source of data is secondary sources. In this study, researchers will systematically collect and analyze samples from all companies within the food and beverage sub sector listed on the IDX. Thus, the research sample consists of all 25 food and beverage companies. A total of 125 samples were gathered and examined for this study over the period of 2018–2022, using unbalance panel data. The study's findings show that, while Return on Asset has a statistically significant and positive relationship with cash holdings in food and beverage companies, Geopolitical Risk, Net Working Capital, and Debt to Asset have a negative relationship and do not significantly affect cash holdings in food and beverage companies listed on IDX, as shown by the F-test result, Prob > F = 0.0000 or less than 0.05. Keywords: Geopolitical Risk, Net Working Capital, Return on Asset, Debt to Asset, and Cash Holding